Establishing nurse-led active surveillance for men with localised prostate cancer: development and formative evaluation of a model of care in the ProtecT trial. Issue 9 (18th September 2015) - Wade, Julia; Holding, Peter N; Bonnington, Susan; Rooshenas, Leila; Lane, J Athene; Salter, C Elizabeth; Tilling, Kate; Speakman, Mark J; Brewster, Simon F; Evans, Simon; Neal, David E; Hamdy, Freddie C; et al.
Abstract : Objectives: To develop a nurse-led, urologist-supported model of care for men managed by active surveillance or active monitoring (AS/AM) for localised prostate cancer and provide a formative evaluation of its acceptability to patients, clinicians and nurses. Nurse-led care, comprising an explicit nurse-led protocol with support from urologists, was developed as part of the AM arm of the Prostate testing for cancer and Treatment (ProtecT) trial. Design: Interviews and questionnaire surveys of clinicians, nurses and patients assessed acceptability. Setting: Nurse-led clinics were established in 9 centres in the ProtecT trial and compared with 3 non-ProtecT urology centres elsewhere in UK. Participants: Within ProtecT, 22 men receiving AM nurse-led care were interviewed about experiences of care; 11 urologists and 23 research nurses delivering ProtecT trial care completed a questionnaire about its acceptability; 20 men managed in urology clinics elsewhere in the UK were interviewed about models of AS/AM care; 12 urologists and three specialist nurses working in these clinics were also interviewed about management of AS/AM. Results: Nurse-led care was commended by ProtecT trial participants, who valued the flexibility, accessibility and continuity of the service and felt confident about the quality of care. ProtecT consultant urologists and nurses also rated it highly, identifying continuity of care and resource savings as key attributes. Clinicians and patients outside the ProtecT trial believed that nurse-led care could relieve pressure on urology clinics without compromising patient care. Conclusions: The ProtecT AM nurse-led model of care was acceptable to men with localised prostate cancer and clinical specialists in urology. The protocol is available for implementation; we aim to evaluate its impact on routine clinical practice. Trial registration numbers: NCT02044172; ISRCTN20141297 .